Strong nasal carcinogenicity and genotoxicity of 1-nitroso-4-methylpiperazine after low dose inhalation in rats - Klein, Reinhold G.; Schmezer, Peter; Spiegelhalder, Bertold; Bartsch, Helmut (Carcinogenesis, 1999)
Sprague-Dawley rats were exposed by inhalation to 1-nitroso-4-methylpiperazine (NMPz) vapor at 2.4 p.p.m. for 15 h/day for 74 days over a 7.5 month period. After a dose of 1.1 mg/day NMPz (total dose 340 mg/kg body wt) 10/10 animals developed tumors of the nasal cavity, mostly invasive muco-epidermoidal carcinomas; no such tumors were observed in sham-exposed controls. This high tumor yield was seen at an 80 times lower dose and a shorter latency period when compared with rat carcinogenicity studies reported earlier. The single cell microgel electrophoresis (Comet) assay was used to determine genotoxicity in target tissues. Short-term in vitro exposure of rat and human nasal epithelial tissues to NMPz caused genotoxic effects in cells of both species. Short-term in vivo exposure of rats to NMPz vapor for 1 h induced DNA damage in nasal epithelial cells. Our results revealed NMPz as a potent genotoxic nitrosamine in rat and human nasal cells, the carcinogenicity of inhaled NMPz vapor in rats being remarkably higher as compared with oral uptake.
Gesehen am 02.02.2021